Teachers’ Constraints in Organizing Learning Process for High School Students in Jambi - Harbeng Masni; Zuhri Saputra Hutabarat; Herman Budiyono (STAI Hubbulwathan Duri, 2022)
The purpose of this study is to describe the constraints faced by high school teachers in Jambi in the students learning process. Those constrains are ranging from planning, implementing, to evaluating learning outcomes. The study was conducted in public high school in Jambi for 8 months. Subjects in this study are subject teachers, principals, supervisors, and supervisors. While the object of this research includes teacher learning documents and infrastructure facilities. This research uses qualitative approach and based on field study. It belongs to phenomenological research and includes descriptive research type. The data were collected using questionnaires, interview guides, observation guides, documentation, and portfolios. The result of the research reveals that public high school teachers in Jambi are experiencing difficulties in planning process of learning. Some hindrances found in the process of implementing student learning in the classroom are the large number of students in each class and the lack of supporting facilities and infrastructure. Whereas the hindrance in the process of evaluating student learning outcomes came from ineffective design qualities.